A study to identify leadership style of nurse managers and influence of leadership style on patient safety culture, organizational citizenship behavior, and job satisfaction so as to suggest an evidence based feed forward for preparing guidelines for training of nurse managers working in a superspecialty tertiary health care teaching institute in Northern India - Rajesh Harsvardhan; Dimpi Singh; S. K. Patnaik; Shabana Khatun (Wolters Kluwer -Medknow Publications, 2023)
Introduction: The safety of patients in health-care systems has long been a concern, but despite many positive changes in practice, health systems, and regulations, the desired level of safety remains unachieved. The competency of health-care leaders to create positive work environments and manage constant change is essential to the success of teams and organizations. The need for great leadership in health care has always been imperative; however, throughout the industry's recent transformation, it has been vital. Faced with enormous amounts of change, today's leaders must be capable of serving their teams while adapting to the evolving landscape and leading us into the future. Aim: The aim of this study was to identify the leadership style of nurse managers and ascertain the influence of leadership style on patient safety culture, organizational citizenship behavior, and job satisfaction so as to suggest an evidence-based feed forward for preparing guidelines for training of nurse managers working in a superspecialty tertiary health-care teaching institute in Northern India. Objectives: The objectives of this study were as follows - (1) to identify the leadership style of nurse managers based on full-range leadership model using the prevalidated tool, (2) to ascertain the influence of leadership style on patient safety culture using the prevalidated tool, (3) to assess the influence of leadership style on organizational citizenship behavior and job satisfaction using the prevalidated tool, and (4) to suggest an evidence-based feed forward for preparing guidelines for training of nurse managers working in a superspecialty health-care teaching institute in India using analysis of data thus obtained. Methodology: This was an analytical study. Results: (1) In the study, it was thus found that as transformational and transactional leadership behavior increases, patient safety culture, organizational citizenship behavior, and job satisfaction also increase; (2) on the other hand, patient safety culture, organizational citizenship behavior, and job satisfaction decrease as laissez-faire leadership behavior increases. Conclusion: Staff nurse under the leadership of their managers provides exemplary care and shares professional knowledge as well as provides direction and support to practice best patient care through policy development.